Effects of nitric oxide on neuromuscular properties of developing zebrafish embryos. - Michael Jay; Sophie Bradley; Jonathan Robert McDearmid (PLoS ONE)
Nitric oxide is a bioactive signalling molecule that is known to affect a wide range of neurodevelopmental processes. However, its functional relevance to neuromuscular development is not fully understood. Here we have examined developmental roles of nitric oxide during formation and maturation of neuromuscular contacts in zebrafish. Using histochemical approaches we show that elevating nitric oxide levels reduces the number of neuromuscular synapses within the axial swimming muscles whilst inhibition of nitric oxide biosynthesis has the opposite effect. We further show that nitric oxide signalling does not change synapse density, suggesting that the observed effects are a consequence of previously reported changes in motor axon branch formation. Moreover, we have used in vivo patch clamp electrophysiology to examine the effects of nitric oxide on physiological maturation of zebrafish neuromuscular junctions. We show that developmental exposure to nitric oxide affects the kinetics of spontaneous miniature end plate currents and impacts the neuromuscular drive for locomotion. Taken together, our findings implicate nitrergic signalling in the regulation of zebrafish neuromuscular development and locomotor maturation.